Cancer disclosure: a cross-cultural research Brazil-Spain - Kern de Castro, Elisa; Peloso, Franciele; Vital, Luísa; Bittencourt Romeiro, Fernanda; Moro Gutiérrez, Lourdes; González Fernández-Conde, Marta (Psicooncología, 2018)
Objective: The aim of this study was to examine cross-cultural aspects of the disclosure of cancer diagnosis in Brazilian and Spanish patients. Method: A qualitative research was carried out in which 28 chemotherapy patients (14 Brazilian and 14 Spanish) were interviewed. Content analysis identified three thematic categories: 1) How the diagnosis was disclosured; 2) Context in which the diagnosis was disclosured; 3) Who disclosured the diagnosis. Results: Particularities in the diagnosis disclosure between the two countries was found. In Brazil, it still happens that patient can be referred to an oncologist without a satisfactory explanation about his health status. Although there are reports of diagnosis disclosure in the appropriate context (consultation), also there are reports informal disclosure (by telephone), without an adequate environment for the patient to be welcomed and able to express their fears and doubts. Conclusion: It is necessary to improve the professional training to improve communication skills and health education to treat cancer patients. Objetivo: examinar aspectos transculturales de la revelación del diagnóstico de cáncer en pacientes brasileños y españoles. Método: Se realizó una investigación cualitativa en la que fueron entrevistados 28 pacientes en quimioterapia (14 brasileños y 14 españoles). El análisis de contenido identificó tres ejes temáticos: 1) Cómo fue revelado el diagnóstico; 2) Contexto en que el diagnóstico fue revelado y 3) Quién reveló el diagnóstico. Resultados: existen particularidades en la manera de revelar el diagnostico entre los dos países. En Brasil aún ocurre que el enfermo puede ser derivado a un oncólogo sin una explicación satisfactoria previa sobre su estado de salud. Aunque en los dos países existan relatos de comunicación de diagnóstico en el contexto apropiado (consulta), también ha aparecido revelación de manera informal (por teléfono) sin un ambiente adecuado para que el paciente sea acogido y tenga posibilidad de expresar sus miedos y sus dudas. ...